Strategi Pencegahan Kebocoran Data Pelayanan Publik Di Era Digital - Soleh, Mohamad; Tjenreng , Zubakhrum (Jurnal Kajian Pemerintah: Journal of Government, Social and Politics, 2025)
Data breaches are one of the major threats to Public Service information security in the digital era. This paper discusses various prevention strategies that can be implemented by organizations to protect sensitive data. Focusing on the importance of encryption, strict access control, and employee training, this paper outlines the steps that must be taken to effectively detect, analyze, and respond to data breach incidents. In addition, it discusses the importance of a comprehensive incident response plan and follow-up to increase organizational resilience to future threats. This paper analyzes various strategies that can be implemented to prevent data breaches, including encryption, access control, and employee training. Analytical methods are used to evaluate the effectiveness of each strategy in the context of the organization. In addition, the importance of an incident response plan is also discussed, with an emphasis on mitigation and recovery steps after an incident. By implementing these best practices, organizations can minimize the risk of data breaches and protect the reputation and trust of stakeholders. The results of the study indicate that a combination of strengthening technological infrastructure, implementing data security policies, and educating users can minimize the risk of data breaches. This study provides strategic recommendations for government agencies in building a safe and reliable public service system.